Terminal Value or Present Value in Capital Budgeting Programs - Jean, William H. (Journal of Financial and Quantitative Analysis, 1971)
In a recent paper by Lusztig and Schwab, a sensitivity analysis was performed on a linear programming capital budgeting problem where selection of projects is based on the criterion of present values. Their model is typical of current practice in the literature, and it is the point of this paper to indicate that a better model exists which allows more flexibility of assumptions and will yield the same results as a present value criterion. The model to be presented here uses a terminal value (horizon value) criterion for selection of the optimum set of investment projects.